Simvastatin attenuates macrophage-mediated gemcitabine resistance of pancreatic ductal adenocarcinoma by regulating the TGF-β1/Gfi-1 axis. (28th January 2017) - Xian, Guozhe; Zhao, Juan; Qin, Chengkun; Zhang, Zhenhai; Lin, Yanliang; Su, Zhongxue
Abstract: Pancreatic ductal adenocarcinoma (PDAC) is a highly lethal malignancy with an intrinsic resistance to almost all chemotherapeutic drugs, including gemcitabine. An abundance of tumor-associated macrophages (TAMs), which can promote the resistance of PDAC to gemcitabine, has been observed in the microenvironments of several tumors. In this study, we confirmed that incubation in TAM-conditioned medium (TAM-CM) reduces the gemcitabine-induced apoptosis of PDAC cells. Simvastatin attenuated the TAM-mediated resistance of PDAC cells to gemcitabine. Further investigation found that simvastatin reversed the TAM-mediated down-regulation of Gfi-1 and up-regulation of CTGF and HMGB1. Simvastatin induced Gfi-1 expression, which increased the sensitivity of PDAC cells to gemcitabine by decreasing TGF-β1 secretion by TAMs. A luciferase reporter assay and ChIP assay revealed that Gfi-1 directly repressed the transcription of CTGF and HMGB1. Simvastatin also reversed the effects of gemcitabine on the expression of TGF-β1 and Gfi-1 and reduced the resistance of PDAC to gemcitabine in vivo. These results provide the first evidence that simvastatin attenuates the TAM-mediated gemcitabine resistance of PDAC by blocking the TGF-β1/Gfi-1 axis. These findings suggest the TGF-β1/Gfi-1 axis as a novel therapeutic target for treating PDAC. Highlights: Simvastatin attenuated TAM-mediated gemcitabine resistance of PDAC cells. Exposure of PDAC cells to TAM-CM inhibited Gfi-1 expression. TAM-CM promoted the expression of CTGF and HMGB1 in PDAC cells. Simvastatin reversed the TAM-mediated signal response. Gfi-1 directly repressed the transcription of CTGF and HMGB1.